Parenthood between generations transforming reproductive cultures - Pooley Siân; Qureshi, Kaveri (Fertility, reproduction and sexuality, 2016)
The chapters situate the cross-cutting power of the life-course in specific global historical contexts, so as to examine how reproductive cultures are influenced by demographic change, new technologies, migration and diaspora. Studies shed light on of the diverse ways in which nature, biology, kinship and gender have been understood.